Investigating a rural community's use of communication technology: a study of Nakaseke Community Multi-media centre in Uganda - Tumusiime, James (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2006)
An assumption that Information and Communication Technologies (ICTs) and economic development have an automatic linkage has gained wide acceptance over the last decade. As a result, developing countries are under pressure to apply this prescription as a solution to poverty. With the help of development partners in the developed world and the United Nations, developing countries have embraced this call to increase access to ICTs to bridge the ever-widening gap between the 'information rich' and 'information poor' (Castells, 2001). One of the strategies has been the establishment of telecentres where the least privileged people might access ICTs for their own development needs. However, this strategy has tended to overlook contextual factors and circumstances in developing countries. ICTs are thus being introduced in an environment of mass poverty, illiteracy and poor infrastructure, exacerbating existing inequalities in some cases. Much attention has been focussed on initiatives aimed at expanding the ICT infrastructure for wider population access without addressing what the users actually do with such access. This study aims to make a contribution in that direction. The study focuses on Nakaseke Community Multi-media Centre(CMC), the first telecentre introduced in Uganda in 1997. Using a combination of quantitative and qualitative research techniques, the study sets out to develop deeper insights into how the Nakaseke community uses, engages with and relates with communication technologies installed at the telecentre. It probes whether these practices advance the dominant view that ICTs are a panacea for rural development. The findings indicate that while access to communication technology has expanded, albeit at a slow pace, the benefits might take very long to have a significant effect as many targeted users do not make use of the facilities because they lack the human skills and financial resources to exploit the technologies. Other problems such as poor electricity supply and sustainability also actively militate against the potential of the project to deliver. Besides, people tend to appropriate technology in ways different from those intended by its promoters. As Burton (2002) explains through the concept of 'affordances' and 'culture', some users perceive technologies essentially as something that bestows the status of being modern or sophisticated on their community, rather than as a development tool. In conclusion, it is argued that if used for development, ICTs can indeed make a difference in the lives of rural people. However, besides investing in technology, there is need to invest more in empowering the people themselves with skills, particularly literacy, to enable them use ICTs productively.
Keywords: Information technology -- Uganda; Media programs (Education) -- Uganda; Communication in rural development -- Uganda; Communication -- Technological innovations -- Developing countries; Telecommuting centres -- Uganda